Osseous Eustachian Tube and Peritubal Cells in Patients With Unilateral Cholesteatoma: Comparison Between Healthy and Diseased Sides Using High-Resolution Cone-Beam Computed Tomography. Issue 5 (June 2015) - Hashimoto, Kengo; Yanagihara, Naoaki; Hyodo, Jun; Sakagami, Masafumi
Abstract : Objectives: We investigated the factors that may possibly cause primary acquired cholesteatoma. Setting: University-affiliated hospital. Subjects and Methods: In 20 adult patients with unilateral cholesteatoma, the sizes of the osseous eustachian tubes (ETs) and the extent of peritubal and mastoid cell development in healthy and diseased ears were examined using high-resolution cone-beam computed tomography. The height and width of the ET were measured at the tympanic orifice, the isthmus, and the midpoint, as was the length of its axis. We also assessed the extent of development of peritubal and mastoid cells. Results: There were no significant differences in the size of the osseous ET between the healthy and cholesteatoma sides, but significant correlations were found in height and width between the sides at the tympanic orifice and at the isthmus. In 80% of ears with cholesteatoma, the development of both peritubal and mastoid cells was poor and, in 5% more, one or the other was poor. Mastoid and peritubal cell development was good in 60% of healthy ears and poor in 20%. In the remaining 20%, only peritubal cell development was poor. Conclusion: There were no significant differences in the size of the osseous ET between the healthy and diseased sides of patients with unilateral cholesteatoma. Our results indicate that inhibition of air cell development in not only the mastoid region but also the peritubal region may contribute to cholesteatoma development.